2007
DOI: 10.1016/j.cpr.2007.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Risk for recurrence in depression

Abstract: Depression is a highly recurrent disorder with significant personal and public health consequences. Prevention of recurrence would be extremely desirable, and thus researchers have begun to identify risk factors that are specific to recurrence, which may be different from risk factors for first-onset of depression. Methodological issues in this area of research are briefly reviewed (e.g., the various definitions of "recurrence" and "depression"), followed by a review of studies on specific risk factors, includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

32
683
6
8

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 842 publications
(765 citation statements)
references
References 124 publications
32
683
6
8
Order By: Relevance
“…Further, it might be that any scarring already occurred before T0 in those with previous episodes, limiting further scarring. Thus, although it may still be too early to discard the idea that scarring occurs altogethermaybe scarring does occur, but in a subtle way (Wichers et al 2010), in subgroups we did not investigate, or in outcome measures we did not investigate (Burcusa & Iacono, 2007;Bhagwagar & Cowen, 2008) -our study suggests there is no robust scarring effect. In contrast to the scarring effects, the vulnerability effects observed in the present study were robust and substantial.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Further, it might be that any scarring already occurred before T0 in those with previous episodes, limiting further scarring. Thus, although it may still be too early to discard the idea that scarring occurs altogethermaybe scarring does occur, but in a subtle way (Wichers et al 2010), in subgroups we did not investigate, or in outcome measures we did not investigate (Burcusa & Iacono, 2007;Bhagwagar & Cowen, 2008) -our study suggests there is no robust scarring effect. In contrast to the scarring effects, the vulnerability effects observed in the present study were robust and substantial.…”
Section: Discussionmentioning
confidence: 76%
“…MDD is a highly recurrent disorder and risk of recurrence is related to the number of previous episodes (Solomon et al 2000;Kessing et al 2004). This observation stimulated the idea that depressive episodes leave more or less permanent residual impairments or scars that confer risk of subsequent episodes; the 'scar hypothesis' (Rohde et al 1990;Burcusa & Iacono, 2007). Indeed, many studies comparing remitted depressed patients with healthy controls have shown that the former differ in certain ways from the latter (Just et al 2001;Bhagwagar & Cowen, 2008;Paykel, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] This interpersonal element Fig. 1 Probability of adherence by group and call-week may have also helped to offset the potentially impersonal and/ or repetitive nature of automated IVR.…”
Section: Discussionmentioning
confidence: 99%
“…Because many patients attribute their depression to insufficient social support, 7 and those with high-quality support have better outcomes, 8,9 it may also be beneficial to intensify the self-management support that patients receive from trusted confidants. While their significant others often provide invaluable assistance, these helpers are at high risk for psychological distress.…”
Section: Introductionmentioning
confidence: 99%
“…Several risk factors for relapse have been identified, for example, early onset, number of previous episodes, residual symptoms, and episode severity (Burcusa & Iacono, 2007;Judd et al, 1998;Kennedy & Paykel, 2004;Paykel, Ramana, Cooper, & Hayhurst, 1995). Potentially modifiable risk factors have been reported as well-including the impact of daily hassles and life events, specific coping styles, decentering, and dysfunctional beliefs (Beshai, Dobson, Bockting, & Quigley, 2011;Bockting, Spinhoven, Koeter, Wouters, & Schene, 2006;Burcusa & Iacono, 2007;Fresco, Segal, Buis, & Kennedy, 2007;Jarrett et al, 2012;ten Doesschate, Bockting, & Schene, 2009).…”
mentioning
confidence: 99%